Smart Rules for Smart Cities Managing Efficient Cities in Euro-Mediterranean Countries - Riva Sanseverino, Eleonora; Riva Sanseverino, Raffaella; Vaccaro, Valentina; Zizzo, Gaetano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book explores the new rules and codes that are required in order to foster the implementation of smart city technologies with a view to meeting the environmental and energy challenges posed by dynamic contemporary cities with increasing populations. In particular, it proposes a methodological approach suitable for use when devising a smart urban/building code for local administrations, taking into account the current European regulatory framework (directives and technical norms) and evaluating the economic feasibility of the suggested measures. A case study is made of a large Mediterranean city in Italy that can be regarded as a paradigm of urban evolution, where a traditional individualism poses a cultural obstacle to the emerging need to share resources. Further features include a smart cities atlas, explanation of how to create local rules for sustainable building restoration/construction, and guidance on economic evaluation of the impact of building automation and passive measures for energy efficiency. The book, which has a multidisciplinary perspective, will be of value to all who are interested in the transition to smart cities that can meet sustainable development targets.
Competitive Urban Models -- Smart Cities Atlas -- The Integration and Sharing of Resources for a New Quality of Living -- Urban Smartness: Tools and Experiences -- The Urban and Environmental Building Code as Implementation Tool -- Economic Feasibility of Measures for Energy Efficiency -- Funding Energy Efficiency Measures.
Keywords: Energy; Energy efficiency; Regional planning; Urban planning; Sustainable development; Environmental economics; Energy; Energy Efficiency (incl. Buildings).; Landscape/Regional and Urban Planning; Sustainable Development; Environmental Economics; Electronic books